1983
DOI: 10.1128/aac.23.2.232
|View full text |Cite
|
Sign up to set email alerts
|

pH-dependent oxacillin tolerance of Staphylococcus aureus

Abstract: A proportion of clinical isolates of Staphylococcus aureus exhibit resistance to bactericidal activity of certain antibiotics, despite normal susceptibility to inhibition. This phenomenon is termed "tolerance." The methodology used to determine tolerance varies greatly. To clarify the relationship between laboratory methodology and tolerance, we determined the minimal bactericidal concentrations and minimal inhibitory concentrations for 20 clinical isolates by two methods. Inocula were prepared by either 3-h g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…While the growth phase may not have a significant effect on MIC tests, as demonstrated by Barry et al (7) and Kim and Anthony (56), most investigators (48,56,70,75,108,114) have confirmed the importance of using log-phase growth for the inoculum for MBC tests. When stationary-phase growth is used, the number of surviving or "persisting" organisms tends to increase after 24 h of incubation, and therefore the MBC result may be artificially high.…”
Section: Introduction Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…While the growth phase may not have a significant effect on MIC tests, as demonstrated by Barry et al (7) and Kim and Anthony (56), most investigators (48,56,70,75,108,114) have confirmed the importance of using log-phase growth for the inoculum for MBC tests. When stationary-phase growth is used, the number of surviving or "persisting" organisms tends to increase after 24 h of incubation, and therefore the MBC result may be artificially high.…”
Section: Introduction Introductionmentioning
confidence: 85%
“…The appearance of bacteriostatic or bactericidal activity is typically determined for each tube in the set, with the result indicating the optimal concentrations of each drug in combination for inhibitory and bactericidal effects. IN (59,67,78,85,99,104,114,120), the use of cation supplements (41,92,107,120), whether the culture is mixed or otherwise agitated during incubation (48,104,105,108,120), the growth phase of the inoculum (7,39,48,57,70,104,105,108,114,120), the pH of the medium (34,105,114,120), the use of serum (binding) proteins (92,120), the presence of complement (21,34,120), the elimination of antibiotic carryover during subculture (8,25,35,47,93,103,104,119,122), the final density of the bacterial inoculum …”
Section: Introduction Introductionmentioning
confidence: 99%
“…In contrast, S. mitis 1, although only slightly less susceptible than S. mitis 2 to the bactericidal effect of amoxicillin, never displayed a reduction of viable counts 419 VOL. 29,1986 on May 11, 2018 by guest http://aac.asm.org/ Downloaded from greater than 3 log10 (>99.9% killing) and therefore had a high MBC. Moreover, since 99.9% killing (delta log CFU, <3) was not achieved with either S. sanguis II or S. mitis 1, these two strains, which exhibited such different susceptibilities to amoxicillin, could both be considered tolerant when defined by the conventional MBC/MIC ratio.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence has gradually accumulated indicating a significant dependency of BDPC results, especially MBCs, on technical factor variations. It is not surprising that factors such as pH (18,38), temperature (30), type of medium (22,28,32), VOL. 28, 1985 on clinical isolates and allegedly oxacillin-tolerant reference strains, Taylor and associates (36) compared results obtained by the standard broth macrodilution BDPC method as outlined in the Manual of Clinical Microbiology with those of a carefully controlled procedure patterned along the lines recommended by Ishida and associates.…”
Section: Methodsmentioning
confidence: 99%